High-Valent d7 NiIII versus d8 CuIII Oxidants in PCET - McDonald, Aidan (My University, 2019)
Oxygenases have been postulated to utilize d4 FeIV and d8 CuIII oxidants in proton-coupled electron transfer (PCET) hydrocarbon oxidation. In order to explore the influence the metal ion and d-electron count can hold over the PCET reactivity, two metastable high-valent metal–oxygen adducts, [NiIII(OAc)(L)] (1b) and [CuIII(OAc)(L)] (2b), L = N,N′-(2,6-diisopropylphenyl)-2,6-pyridinedicarboxamidate, were prepared from their low-valent precursors [NiII(OAc)(L)]− (1a) and [CuII(OAc)(L)]− (2a). The complexes 1a/b–2a/b were characterized using nuclear magnetic resonance, Fourier transform infrared, electron paramagnetic resonance, X-ray diffraction, and absorption spectroscopies and mass spectrometry. Both complexes were capable of activating substrates through a concerted PCET mechanism (hydrogen atom transfer, HAT, or concerted proton and electron transfer, CPET). The reactivity of 1b and 2b toward a series of para-substituted 2,6-di-tert-butylphenols (p-X-2,6-DTBP; X = OCH3, C(CH3)3, CH3, H, Br, CN, NO2) was studied, showing similar rates of reaction for both complexes. In the oxidation of xanthene, the d8 CuIII oxidant displayed a small increase in the rate constant compared to that of the d7 NiIII oxidant. The d8 CuIII oxidant was capable of oxidizing a large family of hydrocarbon substrates with bond dissociation enthalpy (BDEC–H) values up to 90 kcal/mol. It was previously observed that exchanging the ancillary anionic donor ligand in such complexes resulted in a 20-fold enhancement in the rate constant, an observation that is further enforced by comparison of 1b and 2b to the literature precedents. In contrast, we observed only minor differences in the rate constants upon comparing 1b to 2b. It was thus concluded that in this case the metal ion has a minor impact, while the ancillary donor ligand yields more kinetic control over HAT/CPET oxidation.
PUBLISHED